2022
DOI: 10.3390/children9030427
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Role of Physical Activity in Children with Flat Feet by Assessing Subtalar Flexibility and Plantar Arch Index

Abstract: Flat foot is a common pediatric foot deformity which involves subtalar flexibility; it can affect the plantar arch. This study analyzes the evolution of two parameters, i.e., plantar index arch and subtalar flexibility, before and after physiotherapy and orthoses interventions, and examines the correlation between these two parameters. Methods: The study included 30 participants (17 boys, 12 girls, average age 9.37 ± 1.42 years) with bilateral flat foot. We made two groups, each with 15 subjects. Assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…First, by using a cross-sectional design, we cannot determine the causal association between flat feet and physical performance. It is possible that children with lower levels of physical activity may suffer from overweight/obesity, which in addition may lead to flatter feet [ 21 ]. Second, we only included boys in our study, and our results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by using a cross-sectional design, we cannot determine the causal association between flat feet and physical performance. It is possible that children with lower levels of physical activity may suffer from overweight/obesity, which in addition may lead to flatter feet [ 21 ]. Second, we only included boys in our study, and our results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that age [ 13 ], body mass index [ 4 , 5 ], peak height velocity [ 20 ] and physical activity [ 21 ] may mediate the association between flat footedness and physical performance, which we included in adjusted models. Age was self-reported.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand some researchers demonstrate that physiotherapeutic and orthoses interventions result in improved subtalar flexibility and plantar arch index due to their ability to reduce the compensatory role of muscle groups that promote inversion and increase the role of the long perionier muscle [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric flexible flatfoot is usually described as a foot posture with a deficiency in, or the insufficiency of, a longitudinal arch in the midfoot [1,2]. It is regarded as an anatomical variation in the foot structure [3], and clinicians have simply divided this foot posture into painless (asymptomatic flexible flatfoot) and painful (symptomatic flexible flatfoot) [4][5][6][7][8]. This was due to the fact that paediatric flexible flatfoot follows a history of natural improvement over time [8,9] and also because it is easier to reach an agreement for treatment in a child with a symptomatic flexible flatfoot [10].…”
Section: Introductionmentioning
confidence: 99%